The limits of restrictions on free competition in the state of emergency—the Hungarian fuel and food retail price maximisation in the light of the Hungarian constitutional court’s, the Strasbourg court’s and the Luxembourg court’s jurisprudence - Erdős, Csaba; Verebélyi, Viktória; Knapp, László (Frontiers in Political Science, 2025)
Since March 2020, Hungary has almost continuously been under a type of special legal order, the state of emergency, which was first introduced to better protect against the COVID-19 epidemic and then in May 2022—following the amendment of the Fundamental Law—due to the Russian-Ukrainian war. Both the crises caused by the epidemic and the armed conflict in the neighbouring country were de facto limited not only to the health and migration-humanitarian fields, but the Government made use of the exceptional legislative powers of the special legal order in almost all areas of life. Economic regulation was no exception: in 2021, the Government capped the retail price of fuel, and from February 2022 onwards, the retail price of several basic foodstuffs (including flour, sugar, milk, chicken breast and other meats, and later eggs and potatoes). The aim of this paper is to show the limits of one of the most powerful state interventions in the economy: the price maximisation. This can basically be determined on the basis of the relevant case law of three fora of legal protection—the Hungarian Constitutional Court, the European Court of Human Rights in Strasbourg and the Court of Justice of the European Union. A comparison of the case law of the above-mentioned three courts also shows which legal protection mechanism is most effective against legislation restricting the free competition—at least in a period of special legal order.